Handbook of structural steel connection design and details - Tamboli, Akbar R., (McGraw Hill, 1999)
Fasteners for structural connections. Design of connections for axial, moment, and shear forces. Welded joint design and production. Partially restrained connections. Seismic design of connections. Structural steel details. Connection design of special structures. Inspection and quality control. Steel deck details. Connections to composite members.